2008
DOI: 10.1143/jjap.47.1775
|View full text |Cite
|
Sign up to set email alerts
|

Development of Apparatus for Simultaneous Measurements of Raman Spectroscopy and High-Sensitivity Calorimetry

Abstract: Filter radiometers are used as transfer standards in many radiometric measurements, and essentially comprise a detector, filter (interference or coloured glass) and high-precision aperture. An initial study into the use of Fourier-transform (FT) spectrometry has resulted in the attainment of medium accuracy (around 0.3 % to 0.7 %) calibration of assembled filter radiometers in a period of a few hours. This contrasts with a day for characterization using a grating instrument and the weeks required for high-reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 24 publications
2
36
0
Order By: Relevance
“…To determine the general thermal phase behaviours of the samples, calorimetric measurements of sufficiently dried samples (1-2 mg) were performed using a laboratory-made calorimeter with a baseline stability of AE5 mW and a thermal stability of 0.001 K. 34 Measurements for both samples were performed at a scanning rate of 5 mK s À1 for the cooling and heating processes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the general thermal phase behaviours of the samples, calorimetric measurements of sufficiently dried samples (1-2 mg) were performed using a laboratory-made calorimeter with a baseline stability of AE5 mW and a thermal stability of 0.001 K. 34 Measurements for both samples were performed at a scanning rate of 5 mK s À1 for the cooling and heating processes.…”
Section: Methodsmentioning
confidence: 99%
“…[23][24][25]28,29 These phenomena are proved to be closely related to the variety and flexibility of the conformations of the constituent ions. 1,30,31 Many research groups have focused on cations of imidazolium-based RTILs and investigated phase behaviours linked to conformational changes of the substituent groups of each cation, by calorimetry, [22][23][24][25][26][27] Raman spectroscopy 1,26,27,[32][33][34][35] and nuclear magnetic resonance (NMR) analyses. 29,[36][37][38][39][40][41][42][43][44][45][46][47][48] Previously, we revealed a relationship between the thermodynamic properties of imidazolium-based RTILs and their cation dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…(8)]. [19,20] To confirm the further details of the oxidation of 15 a with the nitroxyl-radical catalyst, we determined the time course of the reaction of 15 a and TEMPO in a5:1 molar ratio in MeCN under basic conditions by Raman spectroscopic analysis [21] ( Figure 1). After 1.5 h, peaks assignable to oxoammonium chloride were observed (553.8 and 695.7 cm À1 )t ogether with those of 14 a (541.2 and 797.4 cm À1 ), but peaks attributable to the reduced form of TEMPO (TEMPOH;6 69.6 and 782.1 cm À1 )w ere not detected at all (see the Supporting Information).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The Nishikawa group investigated the premelting behavior of 1-alkyl-3-methylimidazolium salts with a custom-made DSC apparatus with nanowatt sensitivity. [77][78][79][80] They used low heating and cooling rates (typically in the 0.06-0.3 K min À1 range) which allowed measuring under quasi-static conditions. Supported by Raman spectroscopy and gas-phase calculations, they suggested that the broadness of the melting peaks was due to the change between different conformations of the cation's alkyl group.…”
Section: Dsc Calibrationmentioning
confidence: 99%